2013
DOI: 10.1002/ajh.23565
|View full text |Cite
|
Sign up to set email alerts
|

Pain over time and its effects on life in thalassemia

Abstract: Pain reports have become increasingly common and problematic in thalassemia. As patients are living longer, there is a growing need to study pain and explore its impact on patient lives. The Brief Pain Inventory (BPI) was used quarterly to assess pain and pain interference in North American thalassemia patients. The SF-36 and HADS were used to assess quality of life, anxiety, and depression. Of the 252 participants, 56% reported pain at least once over the course of this study, with 32% reporting severe pain (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 19 publications
1
25
0
6
Order By: Relevance
“…Thirty‐seven per cent of patients, report having pain during the past 7 days, while 64% report having pain over the past 4 weeks 49 . Pain seems to interfere with all measures of life activities and to influence the quality of life 50 . The most common site is the lower back, although many patients report pain in various sites, such as legs, upper back or head.…”
Section: The Evolving Spectrum Of Comorbiditiesmentioning
confidence: 99%
“…Thirty‐seven per cent of patients, report having pain during the past 7 days, while 64% report having pain over the past 4 weeks 49 . Pain seems to interfere with all measures of life activities and to influence the quality of life 50 . The most common site is the lower back, although many patients report pain in various sites, such as legs, upper back or head.…”
Section: The Evolving Spectrum Of Comorbiditiesmentioning
confidence: 99%
“…Chronically low hemoglobin (Hb) levels, either in non-transfusion dependent patients or prior to-transfusion have been associated with reduced exercise performance 2,3 . Along with reduced hemoglobin, pain 4 , depression 5,6 , and particularly for children, overprotective parenting can result in reduced physical activity for many patients with…”
Section: Introductionmentioning
confidence: 99%
“…The same investigators later reported on the impact of pain on QoL in a subgroup of participants who also completed the SF‐36 and Hospital Anxiety and Depression Scale (HADS) questionnaires (Fig. ) . The mean scores for most parameters worsened with increasing pain.…”
Section: Prevalence and Characterization Of Pain In Thalassemiamentioning
confidence: 93%